2021
DOI: 10.2147/cmar.s264613
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SLC16A1-AS1 is Upregulated in Glioblastoma and Promotes Cancer Cell Proliferation by Regulating miR-149 Methylation

Abstract: Introduction LncRNA SLC16A1-AS1 has been characterized as a critical player in lung cancer, while its role in glioblastoma (GBM) is unknown. By analyzing the TCGA dataset, we observed the upregulation of SLC16A1-AS1 expression in GBM. Therefore, we aimed to investigate the role of SLC16A1-AS1 in this cancer. Methods GBM tissues and paired non-tumor tissues were collected from 62 GBM patients through biopsy. RT-qPCR was performed to determine the expression of SLC16A1-AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
(43 reference statements)
1
17
0
Order By: Relevance
“…Hence it is important to understand and correlate expression of MCTs and ECMs in different compartments. Our analysis revealed nine differentially expressed MCT genes in both stromal and epithelial samples including the upregulated thyroid hormone (TH) transporters MCT8 (SLC16A12) and MCT10 (SLC16A10), monocarboxylate transporter MCT2 (SLC16A7), MCT6 (SLC16A5) with potential role in glucose and lipid metabolism, and an lncRNA SLC16A1-AS1 previously identified as a prognostic or diagnostic biomarker in a number of cancers [13,[47][48][49][50][51][52][53][54]. To our knowledge, the upregulation of the TH transporters in the stromal-epithelial samples has not been highlighted previously.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hence it is important to understand and correlate expression of MCTs and ECMs in different compartments. Our analysis revealed nine differentially expressed MCT genes in both stromal and epithelial samples including the upregulated thyroid hormone (TH) transporters MCT8 (SLC16A12) and MCT10 (SLC16A10), monocarboxylate transporter MCT2 (SLC16A7), MCT6 (SLC16A5) with potential role in glucose and lipid metabolism, and an lncRNA SLC16A1-AS1 previously identified as a prognostic or diagnostic biomarker in a number of cancers [13,[47][48][49][50][51][52][53][54]. To our knowledge, the upregulation of the TH transporters in the stromal-epithelial samples has not been highlighted previously.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, better understanding of the molecular mechanisms involved in contribution of THs to pancreatic cancer is needed. The lncRNA SLC16A1-AS1 has previously been found to be upregulated in osteosarcoma, glioblastoma and oral squamous cell carcinoma [50, 52, 63], downregulated in non-small cell lung cancer and cervical squamous cell carcinoma [19, 49], and show conflicting expression profile in hepatocellular carcinoma [51, 53, 54]. This is the first study highlighting differential expression of SLC16A1-AS1 in PDAC showing lower levels of expression in epithelial relative to stromal compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is important to understand and correlate the expression of MCTs and ECMs in different compartments. Our analysis revealed nine differentially expressed MCT genes in both stromal and epithelial samples, including the upregulated thyroid hormone (TH) transporters MCT8 ( SLC16A12 ) and MCT10 ( SLC16A10 ), monocarboxylate transporter MCT2 ( SLC16A7 ), MCT6 ( SLC16A5 ) with a potential role in glucose and lipid metabolism, and an lncRNA SLC16A1-AS1 previously identified as a prognostic or diagnostic biomarker in a number of cancers [ 20 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. To our knowledge, the upregulation of the TH transporters in the stromal–epithelial samples has not been highlighted previously.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of SLC16A1-AS1 was observed in hepatocellular carcinoma, and glioblastoma [67,68]. Hong Yue Liu et al suggested that the transcript was dramatically downregulated in non-small cell lung cancer and over expression of SLC16A1-AS1 inhibits the cell viability and proliferation of lung cancer cell [69].…”
Section: Discussionmentioning
confidence: 99%